Livros, discurso e política: como uma aposta dobrada no paradigma de “massas” ancorou, no Brasil, uma coesão “um pouco mais à direita” - Pereira, Thiago Augusto Carlos (Universidade Federal de São Carlos, 2025)
This doctoral thesis investigates the emergence of a right-leaning cohesion that became hegemonic in Brazil around 2013, mirrored in an editorial field typified by trendsetter authors such as Olavo de Carvalho. We begin with Carvalho’s trilogy published between 1994 and 1996, as well as his activity in open courses and newspaper columns, to understand how his work exemplifies a double-down bet on the “masses” paradigm. Carvalho’s writings, we argue, would come to organize the discursive conditions that would later constitute this cohesion and the editorial segment that sustains it. In examining it, we observe that the phenomenon increasingly structures itself through books – taken not merely as vehicles of ideas but as discursive devices of validation, promoting shared meanings and “relations between people” articulated from a position slightly to the right of Brazil’s 1988 democratic framework. Our guiding hypothesis is that this field is discursively and politically structured by a double-down bet on the paradigm of the “masses,” defined, following Jesús Martín-Barbero (1987), as a belief (a) in the ineptitude of the masses, (b) in the inviability of mediations, and (c) in the permanent delegation of historical agency to allegedly superior individuals. The study is organized around three complementary dimensions: (i) an ontological analysis of the book as object—considering its unifying effects, its relation to authorship, and its market aspects; (ii) an editorial genealogy encompassing at least three generations of authors (subscribers and typifiers) of the cohesion; and (iii) a detailed analysis of the mechanisms of discursive regulation that constitute it, beginning with Carvalho’s work, interpreted here as a (pseudo)-epistemological dimension of this double-down bet (as exemplified by the cohesion). Along this path, we also consider the works of Reinaldo Azevedo and Martin Vasques da Cunha—representatives of the segment in the second and third “thirds,” respectively—as well as apologetic productions from the later period (such as those of Escorsim and Berlanza). We demonstrate that this cohesion defines itself by rejecting the common middle ground established by the representative pact of 1988, positioning itself slightly to its right and taking said double-down bet as its synthesis. The doctoral thesis thus contributes to debates on contemporary political culture and on the ways cultural objects—such as the book—operate in favor of ideological arrangements seeking legitimacy at the margins of academia.
Books, discourse, and politics: how a double-down on the “masses” paradigm anchored a cohesion “a little more to the right” in Brazil
Keywords: Análise do Discurso; Livros; Nova Direita Brasileira; Olavo de Carvalho; Populismo; LINGUISTICA, LETRAS E ARTES; 4. Educação de Qualidade; 10. Redução das Desigualdades; 16. Paz, Justiça e Instituições Eficazes